Influence of effective width of flange on calculation and reinforcement dimensioning of beam of reinforced concrete frame - Solarczyk, Maciej Tomasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2021)
The article analyses the impact of modeling the cross-section of two-nave and two-storey reinforced concrete frame with dimensions: 18.0 m × 32.0 m as a bars on the results of bending moments, the value of elastic deflection and dimensioning of reinforcement due to bending. Six options were considered: a beam as a rectangular section and five T-beam variants with different definition of effective flange width. The differences in obtained results were commented. Conclusions useful for the designing of reinforced concrete structures were presented. The procedure for determining the effective flange width in the context of PN-EN 1992-1-1:2008 and PN-B 03264:2002 standards with a commentary on the use of effective flange width in calculations and construction of reinforcement in reinforced concrete structures were described. Brief description of determining the reinforcement due to bending according to simplified method given in PN-EN 1992-1-1:2008 was presented. In addition, the standard formula for determining the minimum cross sectional area of reinforcement (9.1N) in PN-EN 1992-1-1:2008 with a proposal for its strict determination for the T-beam with a flange in the tensile zone was analyzed.